Size-selective neuronal changes in the anterior optic pathways suggest a differential susceptibility to injury in multiple sclerosis. - Evangelou, N; Konz, D; Esiri, M; Smith, S; Palace, J; Matthews, P (2001)
Axonal damage is found in both acute and chronic lesions of multiple sclerosis. Direct axon counting in post-mortem tissue has suggested that smaller axons might have a greater susceptibility to damage, but methodological limitations have precluded unequivocal interpretation. However, as neuronal and axonal sizes are linked and neuronal changes would be expected with retrograde or transsynaptic degeneration following axon injury, we hypothesized that an alternative strategy for studying this phenomenon would be to define multiple sclerosis-associated changes in neurones. To test this hypothesis, we measured both axonal loss and neuronal size changes in the anterior optic pathway [including the optic nerve (ON), optic tract (OT) and lateral geniculate nucleus] of the brains of eight patients who died with multiple sclerosis and in eight control brains. The ONs and OTs in brains from the multiple sclerosis patients showed a trend to smaller mean cross-sectional areas (ON, multiple sclerosis = 6.84 mm(2), controls = 9.25 mm(2); and OT, multiple sclerosis = 6.45 mm(2), controls = 7.94 mm(2), P = 0.08) and had reduced axonal densities (ON, multiple sclerosis = 1.1 x 10(5)/mm(2), controls = 1.7 x 10(5)/mm(2); and OT, multiple sclerosis = 1.4 x 10(5)/mm(2), controls = 1.8 x 10(5)/mm(2), P = 0.006). Estimated total axonal counts were reduced by 32 (OT)-45% (ON) in the patients relative to controls (ON, multiple sclerosis = 8.1 x 10(5) axons, controls = 14.8 x10(5), P = 0.05; and OT, multiple sclerosis = 9.1 x 10(5), controls = 13.3 x 10(5), P = 0.02). The size distributions of the magnocellular cells in the lateral geniculate nucleus were similar for the two groups, but in multiple sclerosis brains the parvocellular cells were significantly smaller (mean sizes: multiple sclerosis = 226 microm(2), controls = 230 microm(2), P < 0.001) and had a larger variation in size, suggesting a greater proportion of atrophic neurones. Axon loss in the optic nerves of multiple sclerosis patients correlated strongly with measures of increased dispersion of cell sizes in the parvocellular layer (r = 0.8, P < 0.04). These data demonstrate that both atrophy and decreased density contribute to the substantial axonal loss in the anterior visual pathway of these patients. This appears related to a relatively selective atrophy of the smaller neurones of the parvocellular layer in the lateral geniculate nucleus, supporting the hypothesis that smaller axons may be preferentially susceptible to injury in multiple sclerosis.